Can Vocational Education Improve the Wages of Minorities and Disadvantaged Groups? The Case of Israel - Shoshana Neuman; Adrian Ziderman (Bar-Ilan University, Department of Economics, 2002)
There is a considerable empirical literature which compares wage levels of workers who have studied at secondary vocational schools with wages of workers who took academic schooling. In general, vocational education does not lead to higher wages. However, in some countries where labor markets are characterized by employment growth, skill shortages and a good match between vocational skills and available jobs, the record of vocational schooling has been more positive. Israel constitutes a case in point. However, little attention has been given to examining the success of vocational education in raising the wages of various sub-sections of the labor force, in particular of minorities and disadvantaged groups. In this paper, we examine the efficacy of vocational education in raising the wage levels of four such groups: recent immigrants, Jews of Eastern origin, Israeli Arabs and females. The results are mixed, differing from group to group, thus justifying our approach of examining the impact of vocational schooling on finer breakdowns of the population of secondary school completers.
Keywords: 330